2004
DOI: 10.4049/jimmunol.173.4.2419
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-Induced Th2 Polarization Is Associated with Down-Regulated Dendritic Cell Responsiveness to Th1 Stimuli and a Transient Delay in T Lymphocyte Cycling

Abstract: The nature of the signals that bias Th effector choice is still not completely understood. Using parasite extracts from pathogens known to induce polarized Th1 or Th2 responses and an in vitro experimental model for priming murine CD4+ cells, we demonstrated that splenic dendritic cells (DC), but not B cells, promote Th1/Th2 differentiation of naive CD4+ lymphocytes. Th polarization in this system was found not to depend on DC secretion of the polarizing cytokines IL-12/IL-4, but instead correlated with distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 70 publications
3
82
1
Order By: Relevance
“…More recently, the same group has found that parasite-induced Th2 responses are related to a dampening of Th1-stimulating immune reactions and a lack of MyD88-signalling. 55 In addition, Sun et al 56,57 have found that Th2 responses arise when Th1 or TLR signals are lacking and, although it has been demonstrated that if IL-4 is blocked following immunization with aluminium a Th1-like response arises, 58 Th2 responses can still be found in the absence of IL-4 or IL-4 signalling in vivo. 26,27 Our microarray experiment, which was based on individual mice, indicates that the initial immune response to Al(OH) 3 is more delayed compared with that of DDA/MPL because metabolic processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the same group has found that parasite-induced Th2 responses are related to a dampening of Th1-stimulating immune reactions and a lack of MyD88-signalling. 55 In addition, Sun et al 56,57 have found that Th2 responses arise when Th1 or TLR signals are lacking and, although it has been demonstrated that if IL-4 is blocked following immunization with aluminium a Th1-like response arises, 58 Th2 responses can still be found in the absence of IL-4 or IL-4 signalling in vivo. 26,27 Our microarray experiment, which was based on individual mice, indicates that the initial immune response to Al(OH) 3 is more delayed compared with that of DDA/MPL because metabolic processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, possible functions of NF-B-dependent MAPK activation in Schistosome Ag-conditioned DC include the induction of factors that would suppress proinflammatory signals (12,22,26) and allow instruction of Th2 cell differentiation. Alternatively, these factors may control proliferative arrest of CD4 ϩ T cells, another pathway that has been proposed to influence Th2 cell differentiation (21).…”
Section: Discussionmentioning
confidence: 99%
“…Schistosome eggs are potent inducers of Th2 responses and in previous studies SEA-pulsed WT DC, although showing minimal up-regulation of classical activation markers were able to prime for Th2 cytokine production (17,20,21). Although no significant differences in expression of MHC class II, CD80, CD86, or CD40 were observed between SEA-pulsed WT and NF-B1 Ϫ/Ϫ DC (data not shown), the ability of NF-B1 Ϫ/Ϫ DC to prime for IL-4 and IL-5 production was lower than WT counterparts (Fig.…”
Section: Nf-b1 ϫ/ϫ DC Fail To Induce Sea-specific Th2 Responsesmentioning
confidence: 99%
See 2 more Smart Citations